1998
DOI: 10.1007/bf02427600
|View full text |Cite
|
Sign up to set email alerts
|

Requests for electromyography from general practitioners and specialists: critical evaluation

Abstract: In order to improve the quality of service and limit costs of a local electromyographic service, the requests for electromyographic (EMG) examination issued by general practitioners and specialists were critically evaluated. The diagnoses suspected by referring doctors were compared with medical history and clinical data to analyze (1) the utility of EMG for the final diagnosis and (2) the concordance with that of the neurophysiologist and with the EMG results. In 1994 and 1995, there were 3482 patients referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
4
22
2
1
Order By: Relevance
“…We do not believe that many of our UNE cases were diagnosed without EMG, because knowledge of the utility of EMG among general practitioners and specialists is relatively high in our area [12] and because there are no other laboratories in the study area. Moreover, because few orthopaedists operated on UNE cases without electrodiagnostic confirmation, as do some orthopaedists in US centres [13,14], and because some cases preferred to undergo surgery outside the Siena area, we also used hospital medical records coded ICD 342.2 and with codes 04.49 or 04.6 of surgical procedures and similarly coded reimbursement records to search for UNE cases.…”
Section: Discussionmentioning
confidence: 96%
“…We do not believe that many of our UNE cases were diagnosed without EMG, because knowledge of the utility of EMG among general practitioners and specialists is relatively high in our area [12] and because there are no other laboratories in the study area. Moreover, because few orthopaedists operated on UNE cases without electrodiagnostic confirmation, as do some orthopaedists in US centres [13,14], and because some cases preferred to undergo surgery outside the Siena area, we also used hospital medical records coded ICD 342.2 and with codes 04.49 or 04.6 of surgical procedures and similarly coded reimbursement records to search for UNE cases.…”
Section: Discussionmentioning
confidence: 96%
“…A study by Mondelli claimed that only 77.2% of the electrodiagnostic evaluations were considered useful by the neurophysiologist substantiating the clinical diagnosis [11]. Podnar found that only 45% of the examinees referred for electrodiagnostic testing were confirmed with dysfunction in the peripheral nervous system [12].…”
Section: Issues With Electrodiagnostics and Reflex Latencymentioning
confidence: 99%
“…Bu sebepten dolayı cinsiyet ayrımı yapılmamıştır. EMG la- [15]. Gereksiz tetkik isteminin azaltılması ise; hastadan ayrıntılı öykü alınabilecek ve eksiksiz klinik muayene yapılabilecek yeterli zamanı ayırmak ile mümkün olabilecektir.…”
Section: Bulgularunclassified